Modelling the Minho river plume intrusion into the rias baixas - Sousa, Magda Catarina Ferreira de (2013)
The Minho River, situated 30 km south of the Rias Baixas is the most important freshwater source flowing into the Western Galician Coast (NW of the Iberian Peninsula). This discharge is important to determine the hydrological patterns adjacent to its mouth, particularly close to the Galician coastal region. The buoyancy generated by the Minho plume can flood the Rias Baixas for long periods, reversing the normal estuarine density gradients. Thus, it becomes important to analyse its dynamics as well as the thermohaline patterns of the areas affected by the freshwater spreading. Thus, the main aim of this work was to study the propagation of the Minho estuarine plume to the Rias Baixas, establishing the conditions in which this plume affects the circulation and hydrographic features of these coastal systems, through the development and application of the numerical model MOHID. For this purpose, the hydrographic features of the Rias Baixas mouths were studied. It was observed that at the northern mouths, due to their shallowness, the heat fluxes between the atmosphere and ocean are the major forcing, influencing the water temperature, while at the southern mouths the influence of the upwelling events and the Minho River discharge were more frequent. The salinity increases from south to north, revealing that the observed low values may be caused by the Minho River freshwater discharge. An assessment of wind data along the Galician coast was carried out, in order to evaluate the applicability of the study to the dispersal of the Minho estuarine plume. Firstly, a comparative analysis between winds obtained from land meteorological stations and offshore QuikSCAT satellite were performed. This comparison revealed that satellite data constitute a good approach to study wind induced coastal phenomena. However, since the numerical model MOHID requires wind data with high spatial and temporal resolution close to the coast, results of the forecasted model WRF were added to the previous study. The analyses revealed that the WRF model data is a consistent tool to obtain representative wind data near the coast, showing good results when comparing with in situ wind observations from oceanographic buoys. To study the influence of the Minho buoyant discharge influence on the Rias Baixas, a set of three one-way nested models was developed and implemented, using the numerical model MOHID. The first model domain is a barotropic model and includes the whole Iberian Peninsula coast. The second and third domains are baroclinic models, where the second domain is a coarse representation of the Rias Baixas and adjacent coastal area, while the third includes the same area with a higher resolution. A bi-dimensional model was also implemented in the Minho estuary, in order to quantify the flow (and its properties) that the estuary injects into the ocean. The chosen period for the Minho estuarine plume propagation validation was the spring of 1998, since a high Minho River discharge was reported, as well as favourable wind patterns to advect the estuarine plume towards the Rias Baixas, and there was field data available to compare with the model predictions. The obtained results show that the adopted nesting methodology was successful implemented. Model predictions reproduce accurately the hydrodynamics and thermohaline patterns on the Minho estuary and Rias Baixas. The importance of the Minho river discharge and the wind forcing in the event of May 1998 was also studied. The model results showed that a continuous moderate Minho River discharge combined with southerly winds is enough to reverse the Rias Baixas circulation pattern, reducing the importance of the occurrence of specific events of high runoff values. The conditions in which the estuarine plume Minho affects circulation and hydrography of the Rias Baixas were evaluated. The numerical results revealed that the Minho estuarine plume responds rapidly to wind variations and is also influenced by the bathymetry and morphology of the coastline. Without wind forcing, the plume expands offshore, creating a bulge in front of the river mouth. When the wind blows southwards, the main feature is the offshore extension of the plume. Otherwise, northward wind spreads the river plume towards the Rias Baixas. The plume is confined close to the coast, reaching the Rias Baixas after 1.5 days. However, for Minho River discharges higher than 800 m3 s-1, the Minho estuarine plume reverses the circulation patterns in the Rias Baixas. It was also observed that the wind stress and Minho River discharge are the most important factors influencing the size and shape of the Minho estuarine plume. Under the same conditions, the water exchange between Rias Baixas was analysed following the trajectories particles released close to the Minho River mouth. Over 5 days, under Minho River discharges higher than 2100 m3 s-1 combined with southerly winds of 6 m s-1, an intense water exchange between Rias was observed. However, only 20% of the particles found in Ria de Pontevedra come directly from the Minho River. In summary, the model application developed in this study contributed to the characterization and understanding of the influence of the Minho River on the Rias Baixas circulation and hydrography, highlighting that this methodology can be replicated to other coastal systems.